DIAGNOSTIC METHODS AND ADVANCEMENTS IN THE DETECTION OF VIRAL INFECTIONS IN ANIMALS - AZAM, MN; KHURSHID, T; GILL, RJ; AHMAD, M; HAIDER, MJ; REHMAN, A; FATIMA, QUA; KHALID, A; NAEEM, M; ABID, H (Biological and Clinical Sciences Research Journal, 2023)
Detecting and diagnosing viral infections in animals play a pivotal role in ensuring the health and well-being of both domesticated and wild species. The study investigates diagnostic methods for detecting viral infections in a diverse animal population (n=300). Employing serological assays, molecular diagnostics, point-of-care testing, and advanced imaging technologies, the research explores sensitivities and specificities of each method. Molecular techniques, particularly PCR and NGS, exhibit consistent high performance, while point-of-care testing and imaging technologies offer practical on-site applications. Demographic considerations enrich the findings, emphasizing the importance of a multidisciplinary approach. This study contributes to refining veterinary diagnostic strategies and advocates for integrating artificial intelligence to address global disparities in diagnostic accessibility.